Ion accumulation, antioxidant activity, growth and tolerance indices of Eucalyptus clones under salt stress - de Andrade, Jailma Ribeiro; de Oliveira Maia Júnior, Sebastião; da Silva, Jônatas Rodrigo Ribeiro; da Silva, Vicente Mota [UNESP]; dos Santos, Claudiana Moura; dos Santos Silva, Lennon Kledson; Endres, Laurício; Ferreira, Vilma Marques (Springer Nature, 2022)
Due to the expansion of planted forests, Eucalyptus may end up being planted in saline soil areas. The aim of this study was to assess ion accumulation, antioxidant activity and the growth and tolerance indices of Eucalyptus clones as indicators of salt tolerance. This study used a randomized block design in a 3 × 4 factorial scheme consisting of three Eucalyptus clones (VC865, I224 and I144) and four concentrations of NaCl (0, 1, 2 and 3 g of NaCl kg−1 of soil) with five repetitions. The Eucalyptus clones responded differently to soil salinity: I144 showed lower declines in Ψw, K+ concentrations, leaf dry weight and stem dry weight. In addition, a lower Ψs was associated with an increase in Na+ and proline and a low Na+/K+ ratio, indicating greater osmotic adjustment. This clone, considered the most tolerant to soil salinity, also exhibited greater superoxide dismutase, ascorbate peroxidase and catalase antioxidant enzymes activity, higher relative increment and tolerance indices and lower hydrogen peroxide and lipid peroxidation content. However, the clones VC865 and I224 are moderately tolerant and sensitive, respectively. Based on the soil salinity variables, Eucalyptus clones were classified in the following order of tolerance: I144 > VC865 > I224.
Keywords: Antioxidant activity; Eucalyptus; Osmotic adjustment; Soil salinity